2018
DOI: 10.1002/jcb.27959
|View full text |Cite
|
Sign up to set email alerts
|

Management of individuals with chronic hepatitis B virus infection and persistent normal or mildly elevated aminotransferase levels

Abstract: No consensus exists with respect to positive hepatitis B virus (HBV) DNA results and persistent normal or mildly elevated alanine aminotransferase (ALT). The aim of this study is to investigate the appropriate management and prognosis of these populations with chronic hepatitis B (CHB). A total of 235 subjects with positive HBV DNA results and persistent normal or mildly elevated ALT were enrolled in this study. Liver biopsy and liver stiffness measurements (LSM) were performed in all participants at baseline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“… 14 In another study, liver biopsy was performed on 235 CHB patients with normal or slightly elevated ALT, in which antiviral treatment was initiated on HBeAg-negative patients. The virological response rate was 90.7% 23 in 72 weeks. After the second liver biopsy, it was found that antiviral treatment could effectively improve the stage of liver fibrosis in CHB patients and reduce cirrhosis occurrence.…”
Section: Discussionmentioning
confidence: 91%
“… 14 In another study, liver biopsy was performed on 235 CHB patients with normal or slightly elevated ALT, in which antiviral treatment was initiated on HBeAg-negative patients. The virological response rate was 90.7% 23 in 72 weeks. After the second liver biopsy, it was found that antiviral treatment could effectively improve the stage of liver fibrosis in CHB patients and reduce cirrhosis occurrence.…”
Section: Discussionmentioning
confidence: 91%
“…A favourable finding in our study was the histological amelioration compared with baseline measurements observed for patients after antiviral therapy. Du et al [ 45 ] and Yan et al [ 46 ] reported that fibrosis scores decreased significantly after long-term therapy for HBeAg-negative CHB patients with either normal or elevated ALT. During our study, paired FibroScan measurements exhibited obvious changes in liver stiffness at 48 weeks and 96 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HBeAg-negative subjects treated with NAs are more likely to obtain a reduction in HBsAg after switching to interferon. 28 A prospective cohort study by Chen et al 29 included 144 HBeAg-negative patients with chronic HBV infection including a treatment group of 102 cases and a control group of 42 cases. Treatment was with PEG-IFN-α alone or in combination with ADV, depending on the HBV DNA load.…”
Section: Drug Choice and Efficacy Evaluation Of Antiviral Therapymentioning
confidence: 99%
“…Yan et al reported that a second biopsy after NA treatment of HBeAg-negative patients with chronic HBV infection and normal or mildly elevated ALTs for 72 weeks showed that antiviral therapy effectively improved liver histology. 28 A study by Xie et al 30 reported that liver stiffness indexes measured by the Fibro-Scan test were distinctly improved by 48 weeks of antiviral treatment in 136 HBeAg-negative patients with chronic HBV infection and normal ALTs. A study conducted by Deng et al 14 included 23 HBeAg-negative patients with chronic HBV infection and obvious inflammation and/or fibrosis in firststage liver pathology who received a second liver biopsy at an interval of 4.5 years.…”
Section: Antiviral Therapy Can Achieve Long-term Benefitsmentioning
confidence: 99%
See 1 more Smart Citation